Knockout of 4.1B triggers malignant transformation in SV40T‐immortalized mouse embryo fibroblast cells. Issue 2 (27th June 2016) - Wang, Zi; Zhang, Jingxin; Zeng, Yayue; Sun, Shuming; Zhang, Ji; Zhang, Bin; Zhu, Min; Ouyang, Ruoyun; Ma, Bianyin; Ye, Mao; An, Xiuli; Liu, Jing
Abstract : Protein 4.1B deficiency has been found to promote the tumor development; however, whether 4.1B deficiency participates in malignant transformation is unknown. In this study, we demonstrated that 4.1B gene deletion was sufficient to transform SV40T antigen‐immortalized mouse embryonic fibroblasts (iMEFs), as reflected by the ability of 4.1B −/− iMEFs to growth in the environments that were growth restrictive for 4.1B +/+ iMEFs and to form tumors in nude mice, whereas 4.1B +/+ iMEFs were unable to form tumors in vivo. The histological examination revealed that the tumors generated by 4.1B −/− iMEFs were desmoid tumors with features of local invasion. Moreover, loss of 4.1B significantly accelerated cell cycle progression, accompanied by activation of typical proto‐oncogene ERK, AKT, and the G1/S regulatory pathway (p16 INK4A ‐pRb pathway), and up‐regulation of many members of the Wnt gene family. In particular, 4.1B −/− iMEFs exhibited nuclear accumulation of β‐catenin, which is an indicator for desmoid tumor, with down‐regulation of E‐cadherin expression and up‐regulation of snail, zeb1, and vimentin expression, indicating that EMT potentially occurred in transformed 4.1B −/− iMEFs. Moreover, we showed that 4.1B interacted with E‐cadherin in MEF cells. Thus, our study provides previously unidentified roles and mechanisms of 4.1B in cellular transformation. © 2016 Wiley Periodicals, Inc.